Human tendon-derived cell sheets created by magnetic force-based tissue engineering hold tenogenic and immunomodulatory potential. (1st September 2021) - Vinhas, Adriana; Gonçalves, Ana I.; Rodrigues, Márcia T.; Gomes, Manuela E.
Abstract: Cell sheet technology and magnetic based tissue engineering hold the potential to become instrumental in developing magnetically responsive living tissues analogues that can be potentially used both for modeling and therapeutical purposes. Cell sheet constructions more closely recreate physiological niches, through the preservation of contiguous cells and cell-ECM interactions, which assist the cellular guidance in regenerative processes. We herein propose to use magnetically assisted cell sheets (magCSs) constructed with human tendon-derived cells (hTDCs) and magnetic nanoparticles to study inflammation activity upon magCSs exposure to IL-1β, anticipating its added value for tendon disease modeling. Our results show that IL-1β induces an inflammatory profile in magCSs, supporting its in vitro use to enlighten inflammation mediated events in tendon cells. Moreover, the response of magCSs to IL-1β is modulated by pulsed electromagnetic field (PEMF) stimulation, favoring the expression of anti-inflammatory genes, which seems to be associated to MAPK(ERK1/2) pathway. The anti-inflammatory response to PEMF together with the immunomodulatory potential of magCSs opens new perspectives for their applicability on tendon regeneration that goes beyond advanced cell based modeling. Statement of significance: The combination of cell sheets and magnetic-based technologies holds promise as instrumental bio-instructive tools both for tendon disease modelling and for the development of magnetically responsive living tendon substitutes. We have previously shown that remote actuation of a pulsed electromagnetic field (PEMF) modulated the inflammatory response of IL-1β-treated human tendon-derived cell (hTDCs) monolayers. As magnetic cell sheets (magCSs) technologies enable improved cellular organization and matrix deposition, these constructions could better recapitulate tendon niches. In this work, we aimed to apply magCSs technologies to study hTDCs responses in inflammatory environments. Overall results show that PEMF-stimulated-magCSs hold evidence for immunomodulatory properties and to become a living tendon model envisioning tendon regenerative therapies. Graphical abstract: Image, graphical abstract